Beneficiamento da flor do mangará da bananeira (Musa x paradisiaca) e o desenvolvimento de conservas - Silva Neto, Pedro Abreu da (2023)
The banana plant (Musa ssp.) is known for providing one of the most consumed fruits in Brazil, the banana. Despite the food and fruit potential of the banana plant, it is possible to find other edible parts in the structure of this plant, such as the banana blossom, an inflorescence generated below the banana cluster, which can be considered an Unconventional Food Plant (UFP). Despite its food potential, the banana blossom has a strong presence of annins in its flavor and undergoes rapid oxidation when processed, which necessitates processing to reduce tannins and preserve its visual and sensory characteristics regarding oxidation. Therefore, this research aimed to develop a processing method for the banana blossom flowers to maintain their physical and sensory qualities with potential applicability in food. To achieve this, three stages were carried out for process definition: physical characterization of the banana blossom for gross weight, net weight, and length verification; reduction of oxidation using soaking in different solutions (alcohol vinegar, citric acid, baking soda, water only, water with salt); and reduction of tannin flavor, following the same parameters with soaking and cooking added. With the standardization of these processes, three preserves were developed: the banana blossom preserve in water (BPW), the banana blossom preserve in vinegar (BPV), and the banana blossom pickle (BBP), to assess which one would maintain the best characteristics and could be used as products for appetizers and snacks, such as caponata, relish, tempura, and fried the banana blossom chips. After preparation, these preserves underwent physical-chemical characterization, quantification of antioxidant capacity using the ABTS+ method, and sensory evaluation through a focus group with gastronomy professionals. Moisture and ash analyses showed averages of 89,79 and 0.06 mg, respectively, for the sample in natura. BBP had the highest titratable acidity (2.76 mg), soluble solids (4.0 ± 0.1 °Brix), and proteins (0.45 ± 0.01%). Only BPV and BBP were below the pH value of 4.5 required by current legislation (RDC N° 352 of December 23, 2002). BPV and BBP showed similar lipid content (0.004%). Colorimetric analysis revealed differences in the BBP sample compared to the others in terms of a*, c*, and h*, while MPV differed from L*, with none of the samples differing in terms of b*. The average values of the antioxidant activity analysis indicated that BPV (10.01 µg/mL) and BBP (7.87 µg/mL) were statistically similar (p > 0.05). Sensory analysis revealed different functionalities for vinegar and pickle preserves, with both being accepted for consumption and use according to the evaluators. The standout appetizer was the banana blossom caponata sample. The development of the banana blossom flower processing protocol proved to be feasible, showing a reduction in tannin flavor and maintaining physical characteristics without oxidation.